Insights into CSF-1R Expression in the Tumor Microenvironment - Caterina Tomassetti; Gaia Insinga; Francesca Gimigliano; Andrea Morrione; Antonio Giordano; Emanuele Giurisato (Biomedicines)
The colony-stimulating factor 1 receptor (CSF-1R) plays a pivotal role in orchestrating cellular interactions within the tumor microenvironment (TME). Although the CSF-1R has been extensively studied in myeloid cells, the expression of this receptor and its emerging role in other cell types in the TME need to be further analyzed. This review explores the multifaceted functions of the CSF-1R across various TME cellular populations, including tumor-associated macrophages (TAMs), myeloid-derived suppressor cells (MDSCs), dendritic cells (DCs), cancer-associated fibroblasts (CAFs), endothelial cells (ECs), and cancer stem cells (CSCs). The activation of the CSF-1R by its ligands, colony-stimulating factor 1 (CSF-1) and Interleukin-34 (IL-34), regulates TAM polarization towards an immunosuppressive M2 phenotype, promoting tumor progression and immune evasion. Similarly, CSF-1R signaling influences MDSCs to exert immunosuppressive functions, hindering anti-tumor immunity. In DCs, the CSF-1R alters antigen-presenting capabilities, compromising immune surveillance against cancer cells. CSF-1R expression in CAFs and ECs regulates immune modulation, angiogenesis, and immune cell trafficking within the TME, fostering a pro-tumorigenic milieu. Notably, the CSF-1R in CSCs contributes to tumor aggressiveness and therapeutic resistance through interactions with TAMs and the modulation of stemness features. Understanding the diverse roles of the CSF-1R in the TME underscores its potential as a therapeutic target for cancer treatment, aiming at disrupting pro-tumorigenic cellular crosstalk and enhancing anti-tumor immune responses.